The Effectiveness of Red Ginger Water Bath to Reduce Blood Pressure of Pregnant Women with Preeclampsia - Asmarita Jasda; Romalina Romalina (Aloha International Journal of Health Advancement (AIJHA), 2024)
Pre-eclampsia is pregnant women with pre-eclampsia at gestational age > 20 weeks, urine protein levels ≥30 mg per 24 hours, and systolic blood pressure >140 mmHg or diastolic blood pressure ≥90 mmHg. Pre-Eclampsia could begin in the antenatal, intrapartum, or postpartum period. Management of pre-eclampsia generally aims to avoid eclampsia and stop the injury/trauma to the mother and fetus, the birth of the baby who can grow and develop normally, and the full recovery of the mother's health. Management of pre-eclampsia can be pharmacological and non-pharmacological. This study aimed to determine whether giving foot soak therapy using red ginger water decoction affects reducing blood pressure in pregnant women with pre-eclampsia. The design of this study was quasi-experimental with a pre-test and post-test design. This study used a non-probability sampling technique with a purposive sampling method of 40 respondents. Soaking feet using boiled red ginger water implemented for 2 weeks. In the analysis of data, the Mann-Whitney test was used. The results showed that most respondents were 31-40 years old, had higher education, were employed (55%), and were on Gravida III. Most respondents had a medical history of hypertension in both the control and intervention groups. The results of the Mann-Whitney test for systolic pressure, p-value 0.000 (